Structure of ThiM from Vitamin B1 biosynthetic pathway of Staphylococcus aureus - Insights into a novel pro-drug approach addressing MRSA infections - Drebes, Julia; Künz, Madeleine; Windshügel, Björn; Kikhney, Alexey G.; Müller, Ingrid B.; Eberle, Raphael J. [UNESP]; Oberthür, Dominik; Cang, Huaixing; Svergun, Dmitri I.; Perbandt, Markus; Betzel, Christian; Wrenger, Carsten (Springer Nature, 2016)
Infections caused by the methicillin-resistant Staphylococcus aureus (MRSA) are today known to be a substantial threat for global health. Emerging multi-drug resistant bacteria have created a substantial need to identify and discover new drug targets and to develop novel strategies to treat bacterial infections. A promising and so far untapped antibiotic target is the biosynthesis of vitamin B1 (thiamin). Thiamin in its activated form, thiamin pyrophosphate, is an essential co-factor for all organisms. Therefore, thiamin analogous compounds, when introduced into the vitamin B1 biosynthetic pathway and further converted into non-functional co-factors by the bacterium can function as pro-drugs which thus block various co-factor dependent pathways. We characterized one of the key enzymes within the S. aureus vitamin B1 biosynthetic pathway, 5-(hydroxyethyl)-4-methylthiazole kinase (SaThiM; EC 2.7.1.50), a potential target for pro-drug compounds and analyzed the native structure of SaThiM and complexes with the natural substrate 5-(hydroxyethyl)-4-methylthiazole (THZ) and two selected substrate analogues.